(untitled) (Scientific journal of the Fergana State University, 2023)
V state privedeny results of morphobiological pokazateley goltsa Kushakevicha (Iskandaria kuschakewitschi) iz Shakhrihansaya protekayushchii po Ferganskoy doliny. Analysis of the current taxonomic status and distribution of this species (suborder Cobitoidei, family Nemacheilidae; genus Iskandaria) in the Fergana Valley.